Muscle Diseases of Metabolic and Endocrine Derivation - Bruce Rothschild (Rheumato)
Muscle function and pathology are complex subjects; the medical fields involved in their diagnosis and treatment represent rheumatology, physiatry and metabolic disease, among others. While we, rheumatologists, concentrate our efforts predominantly on inflammatory varieties and those associated with medications (e.g., corticosteroid and statin use), we are often the “turn to” gatekeepers for the identification of the diagnostic category represented by a patient’s symptomatology. The broad base of rheumatologic training prepares us for the recognition of endocrinologically derived myopathy. This subject and fundamentally biochemically derived myopathies form the basis for this review.